2015
DOI: 10.1136/bcr-2014-208488
|View full text |Cite
|
Sign up to set email alerts
|

Proximal-type epithelioid sarcoma—unusual presentation: unilateral vulvar mass

Abstract: Epithelioid sarcoma of the vulva is a very rare malignant soft tissue tumour, usually initially asymptomatic, which simulates a variety of benign lesions, leading to diagnosis only at later stages. Prognosis is generally poor. We report a case of a 55-year-old postmenopausal woman, who presented with rapid growth of an asymptomatic mass located in the left labia majora. Biopsy of the lesion revealed features characteristic of proximal-type epithelioid sarcoma. Ganglionar, adrenal, pulmonary and hepatic metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 10 publications
0
26
0
2
Order By: Relevance
“…Therefore, approximately one-third of these cases are initially misdiagnosed as a Bartholin’s gland cyst or abscess ( Matsuo et al, 2009 ), as observed in this case. Misdiagnosis often leads to tumor progression and worse prognosis due to delayed treatment ( Altundag et al, 2004 , Matsuo et al, 2009 , Rodrigues et al, 2015 , Tjalma et al, 1999 ). The mean age of PES occurrence is approximately 27.8–35 years, similar to that in patients with other sarcomas ( Altundag et al, 2004 , Matsuo et al, 2009 , Rodrigues et al, 2015 , Tjalma et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, approximately one-third of these cases are initially misdiagnosed as a Bartholin’s gland cyst or abscess ( Matsuo et al, 2009 ), as observed in this case. Misdiagnosis often leads to tumor progression and worse prognosis due to delayed treatment ( Altundag et al, 2004 , Matsuo et al, 2009 , Rodrigues et al, 2015 , Tjalma et al, 1999 ). The mean age of PES occurrence is approximately 27.8–35 years, similar to that in patients with other sarcomas ( Altundag et al, 2004 , Matsuo et al, 2009 , Rodrigues et al, 2015 , Tjalma et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Malignancies of the vulva are rare ( Altundag et al, 2004 ). Particularly, proximal-type epithelioid sarcoma (PES) of the vulva is extremely rare; it accounts for only 1–3% of vulvar malignancies ( Rodrigues et al, 2015 , Tjalma et al, 1999 ). However, clear management guidelines and optimal therapies for this malignancy have not been established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first case of PES of the vulva was described by Pier et al in 1972 [ 8 ]. It often affects the labia majora of young women, and its differential diagnoses include Bartholin’s cyst, lipoma, and genital warts [ 7 , 9 ]. Its benign appearance as an asymptomatic subcutaneous nodule poses diagnostic and therapeutic dilemmas for clinicians [ 8 - 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The histological type of VS is heterogeneous and mainly includes leiomyosarcoma, dermato brosarcoma protuberans, angiosarcoma, rhabdomyosarcoma and epithelioid sarcoma [3,4]. Unlike other vulvar malignancies, VS usually grows with benign appearance and non-speci c manifestation, which increases the di culty of early diagnosis [5]. The biological behavior of VS is featured by frequent recurrence and high potential to metastasize, for which the initial treatment is quite important [6].…”
Section: Introductionmentioning
confidence: 99%